Pengaruh Setting kawasan Tamansari terhadap Temperature Humidity Index - Astuti, Adindra Maharsi Kusuma; Feriadi, Henry (ATRIUM: Jurnal Arsitektur, 2024)
Title: The Effect of Environmental Setting of Tamansari on Temperature Humidity Index Geometric shape, land cover type, and density impact increasing global temperature and microclimate comfort. Tamansari was originally a park, garden, and bathhouse for the King and his family.  Today, Tamansari is a heritage tourism area surrounded by dense residential areas in the middle of Yogyakarta City. This study aims to determine how the setting of the Tamansari area affects changes in temperature and relative humidity, which impact changes in the Temperature Humidity Index (THI) on the micro-scale of the Tamansari area. The method used is descriptive quantitative analysis, and calculation analysis was performed using the (THI) equation. The study results showed that the THI value in the Tamansari area was uncomfortable, with a THI value of 27.77-32.52°C. Building coverage ratio, population, and human activities affect the THI value. The THI value can also change due to weather factors that affect the physical condition of the area, especially in open areas.